2018
DOI: 10.1139/cjas-2017-0053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a matrix-coated organic acids and medium-chain fatty acids blend on performance, and in vitro fecal noxious gas emissions in growing pigs fed in-feed antibiotic-free diets

Abstract: This study evaluated the efficacy of a matrix-coated organic acids and medium-chain fatty acids blend (MCOFA) in growing pigs. Ninety six pigs [(Yorkshire × Landrace) × Duroc] with an average body weight (BW) of 47.71 ± 3.73 kg were used in a 6 wk experiment. Pigs were allotted to diets containing 0 or 2 g kg−1 of MCOFA, and 0 or 2.5 g kg−1 of antibiotic growth promoters (AGP) according to a 2 × 2 factorial arrangement of treatments. Pigs fed diets supplemented with MCOFA had improved growth efficiency compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Therefore, no comparisons could be made with other studies. In pigs, it has been reported that using the same product (blend of OAs and MCFAs) decreased the NH 3 gas emission [8,29]. The reduction in NH 3 gas emission could possibly be due to a decline in the pathogenic bacterial population in the gastrointestinal tract or due to enhancement of beneficial microbial activity, leading to changes in end products of microbial fermentation and a shift in the ecosystem towards being more ecofriendly [29].…”
Section: Gas Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, no comparisons could be made with other studies. In pigs, it has been reported that using the same product (blend of OAs and MCFAs) decreased the NH 3 gas emission [8,29]. The reduction in NH 3 gas emission could possibly be due to a decline in the pathogenic bacterial population in the gastrointestinal tract or due to enhancement of beneficial microbial activity, leading to changes in end products of microbial fermentation and a shift in the ecosystem towards being more ecofriendly [29].…”
Section: Gas Emissionmentioning
confidence: 99%
“…Although organic acids have positive effects on growth performance, intestinal microbial growth and health status in animals, the activities of OAs without any protection would be limited due to prompt absorption and metabolism, or both, before undergoing chemical digestion upon entering the duodenum, which eventually inhibits the modulation of intestinal flora [8]. To improve the retention time of nutrients and active compounds in food and drugs, microencapsulation or matrix coating technology was developed, which can slow down the release of those compounds through the gut, in order to enable them to reach the distal part of the intestine in appreciable and effective amounts [9].…”
Section: Introductionmentioning
confidence: 99%
“…Smulikowska et al (2009) noted that supplementation of protected OA in animal diet improved N retention compared to control diet [ 41 ]. Previous studies also indicated that pigs feed protected OAs supplementation has improved the growth performance [ 10 , 35 , 36 ], nutrient digestibility [ 11 , 35 ], and microflora counts [ 35 ].…”
Section: Protected Organic Acidsmentioning
confidence: 99%
“…Lactic acid has been reported to reduce gastric pH and delay the multiplication of an enterotoxigenic Escherichia coli (E. coli) [8] and to be more effective than other OAs in improving the growth performance of pig [9]. Other studies have demonstrated that, under normal physiological conditions, dietary inclusion of OAs was beneficial to swine and improved growth performance and reduced the post-weanling diarrhea in piglets challenged with E. coli K88 [10], reduced fecal pH and increased serum lymphocyte concentrations, and improved growth performance of growing pigs [11] The most commonly used organic acids are short chain fatty acids, e.g., formic acid, propionic acid, butyric acid, acetic acid, citric acid, and malic acid, which is a dicarboxylic acid. These all are usually weak organic acids, which, when dissolved in water, change into their hydrogen and hydroxyl ion, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation